Environmental education through outdoor education for primary school children - Azlinawati Abdullah,; Sharifah Zarina Syed Zakaria,; Muhammad Rizal Razman, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
Global environmental education has long been introduced as early as the 18th century, but in Malaysia, it still can be considered as a new start, in the year 1979. Since then, various plans and programs have been implemented to produce environmentally literate society, involving school, local and international community. However, awareness and attitudes towards the environmental sustainability amongst Malaysians are still far behind compared to some other developed countries such as Japan, South Korea and Australia, though we are getting closer to the goal of Vision 2020 to become a developed country. Environmental education taught in primary schools in Malaysia is a cross-curricular subject, but its effectiveness on the level of knowledge, awareness and attitude of the environment amongst students are still low. Therefore, this research will identify: (i) the relationship between environmental education with outdoor education, and (ii) the importance and impact of this relationship to increase students’ knowledge, awareness and attitude of the environment. The objective of this study is to generate an understanding of the implementation of outdoor education as an effective method and why it is said to be one of the best ways to educate children about the environment. Based on case studies in Malaysia, the level of knowledge and awareness of school children on the environment are presented. Results of these studies are useful for the development of effective implementation of environmental education programs. The last part outlines the importance of outdoor education to teach environmental education to pupils in primary schools.